2017
DOI: 10.1101/232975
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Isolation of nucleic acids from low biomass samples: detection and removal of sRNA contaminants

Abstract: Sequencing-based analyses of low-biomass samples are known to be prone to misinterpretation due to the potential presence of contaminating molecules derived from laboratory reagents and environments.Due to its inherent instability, contamination with RNA is usually considered to be unlikely. Here we report the presence of small RNA (sRNA) contaminants in widely used microRNA extraction kits and means for their depletion. Sequencing of sRNAs extracted from human plasma samples was performed and significant leve… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 66 publications
(74 reference statements)
1
9
0
Order By: Relevance
“…A previous report suggested that miR analysis may be confounded by contamination of NucleoSpin miR plasma columns with microbial RNAs, but we could not reproduce these findings [30]. We tested for column contamination by passing molecular biology grade water through hypochlorite-treated and non-treated columns and compared the Ct values of the six miRs in the two treatments by RT-qPCR (n = 5 per treatment).…”
Section: Plasma Levels Of Immune-related Mirsmentioning
confidence: 99%
See 3 more Smart Citations
“…A previous report suggested that miR analysis may be confounded by contamination of NucleoSpin miR plasma columns with microbial RNAs, but we could not reproduce these findings [30]. We tested for column contamination by passing molecular biology grade water through hypochlorite-treated and non-treated columns and compared the Ct values of the six miRs in the two treatments by RT-qPCR (n = 5 per treatment).…”
Section: Plasma Levels Of Immune-related Mirsmentioning
confidence: 99%
“…MiRs were isolated from plasma by using the NucleoSpin miRNA plasma kit (Macherey-Nagel) and assayed by reverse transcription quantitative PCR (RT-qPCR) as described above. Heintz-Buschart et al reported that spin columns for RNA purification may be contaminated with microbial RNAs and produce false positive results in miR analysis [30]. Although we could not reproduce contamination of spin columns, we opted to err on the side of caution and purified columns with 0.5% sodium hypochlorite prior to use [30].…”
Section: Plasma Mir Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Recent work has highlighted that commercial DNA/RNA extraction kit reagents, typically designed for high-biomass environments, contain their own microbiome that can skew downstream amplicon data analyses (46,47). It is also important to remove reagent contamination from SAGs, metagenomes, and metatranscriptomes (48)(49)(50). Thus, great care must be taken to screen resulting reads and assembled contigs to identify and remove suspicious sequences, while also allowing that sometimes organisms that were previously thought to represent surface contamination, such as cyanobacteria, may actually be legitimate community members (51).…”
Section: Genetic Potential Of Subsurface Environmentsmentioning
confidence: 99%